FLIPPED CLASSROOM AND KAHOOT IN PHYSICS LEARNING: IMPROVING STUDENTS’ MOTIVATION LEARNING - Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi; Sumarni, Ria Asep; Sulisworo, Dwi; Toifur, Moh (Universitas Ahmad Dahlan, 2021)
Ideal condition in physics learning should combine concepts with technology. Traditional physics learning causes students to be not interested in learning physics. There must be innovations in physics learning to be more interactive learning. One of them flipped classroom learning. Flipped classroom learning combined with Kahoot online games will make students more active. The purpose of this research is to increase students' learning motivation with Kahoot-based flipped classroom learning. The method used in this research is the quasi-experimental method with the research design of The Randomized Post-Test Only Control Group Design. The research finding can describe as follows: First, the flipped classroom is learning the model that combines face-to-face with e-learning to improve students' motivation in physics learning. Second, Kahoot in a flipped classroom supported as an evaluation model. Third, three main steps in applying the flipped classroom are preparing,Â implementing, and evaluating the design.